P147 Solriamfetol Titration & AdministRaTion (START): Characteristics of patients with obstructive sleep apnoea (OSA) and prescriber rationale for starting treatment with solriamfetol. (7th October 2021) - Singh, H; Hyman, D; Parks, G; Chen, A; Foley, C; Ito, D; Thorpy, M
Abstract: Introduction: Solriamfetol (Sunosi) is a dopamine/norepinephrine reuptake inhibitor approved (EU/US) to treat excessive daytime sleepiness (EDS) in adults with OSA (37.5–150 mg/day) or narcolepsy (75–150 mg/day). This study examined characteristics of patients with OSA initiating solriamfetol and prescribers' rationales. Methods: This descriptive study included a retrospective patient chart review among US-based physicians prescribing solriamfetol for patients with OSA/narcolepsy. Solriamfetol initiation strategies were classified as de novo (no prior EDS medication), transition (switched/switching from existing EDS medications), or add-on (adding to current EDS medication). Results: Physicians (n=24) entered data from 50 patients with OSA (mean+/-SD age, 52+/-9.1 years; 62% male). EDS was primarily moderate (56%) or severe (36%). Mean+/-SD Apnea-Hypopnoea Index at OSA diagnosis was 33.1+/-19.7 (n=37). The most common nonpharmacologic treatment was positive airway pressure (n=39, 78%); 36/39 (92%) were considered adherent. Common comorbidities included obesity (BMI>/=30) (n=25, 50%), cardiovascular disorders (n=16, 32%), and type 2 diabetes (n=14, 28%). Twenty-two (44%) patients were de novo, 26 (52%) transitioned (primarily from wake-promoting agents [18/26, 69%]), and 2 (4%) added solriamfetol (to stimulants). The efficacy of solriamfetol prompted most discussions to prescribe de novo (18/22, 82%); a desire for improved efficacy and/or augmentation of other medications prompted most transitioning (15/26, 58%) and add-on (2/2, 100%) therapy. At data collection, 48 (96%) patients were stable on solriamfetol; one each discontinued due to lack of efficacy and side effects. Discussion: Efficacy was a key consideration for physicians prescribing solriamfetol for EDS in a real-world sample of patients with OSA. Support: Jazz Pharmaceuticals